Using Multimission Satellite Altimetry to Monitor Subglacial Hydrological Activities in the Totten Basin, East Antarctica - Jun Liu; Lihui Chen; Denghui Tang; Huan Xie; Xiangbin Cui; Peinan Li (IEEE Journal of Selected Topics in Applied Earth Observations and Remote Sensing)
In East Antarctica, the largest thinning rates are observed at Totten Glacier in recent years. Hydrologic activity of the three active subglacial lakes (Totten1, Totten2, and Wilkes1) located on Totten Glacier may affect the ice sheet mass balance in the region on time scales of decades. In this article, we utilized laser altimetry data (ICESat and ICESat-2) and radar altimetry data (CryoSat-2 and Sentinel-3) to establish a 20-year time series of surface ice sheet elevation changes for three subglacial lakes, employing different least squares fitting methods, and this analysis aimed to study their hydrological activities. Additionally, we combined REMA and BedMachine data to acquire the subglacial drainage pathways in the region, analyzing the hydrological connections among the three subglacial lakes. The results indicate that Totten1 and Totten2 exhibited frequent inflow and outflow throughout the observation period, with periodic characteristics in lake activities. From 2003 to 2009, Wilkes1 showed an ascending trend in surface ice sheet elevation, followed by a relatively stable state. The characteristics of lake activities changes and subglacial drainage pathways indicate connections among these three subglacial lakes. This article highlights that CryoSat-2 and Sentinel-3 radar data can fill the gaps between ICESat and ICESat-2 data. Furthermore, ICESat-2 laser altimetry data not only extend the records of subglacial lake activities but also capture more densely and accurately resolved spatial details. The integration of these four altimeters proves effective for long-term monitoring of active subglacial hydrological activities.